Audiovisual and digital ethnography a practical and theoretical guide - Grasseni, Cristina 1971-; Barendregt, Bart 1968-; Maaker, Erik de 1963-; Musso, Federico de; Littlejohn, Andrew; Maeckelbergh, Marianne; Postma, Metje; Westmoreland, Mark R. (Routledge, 2022)
Audiovisual and digital ethnography at Leiden -- Learning to see -- Sonic ethnography -- Graphic anthropology: A foundation for multimodality -- Dialogic events: An audiovisual toolkit for extended participatory observation -- Observational cinema as process, skill and method -- Interactive documentaries -- Digital ethnography, or 'Deep Hanging Out' in the age of big data -- Navigating conflicting instruments of data morality
Literaturangaben
Keywords: Neue Medien; Ethnologie; Visuelle Ethnologie; Forschungsmethode; Ethnology; Ethnology / Technological innovations; Digital media; Audio-visual materials; Aufsatzsammlung